Participation in outdoor recreational activities and cultural identity in Australia: An exploratory qualitative study - Maniam Vegneskumar; Brown Russel (Sciendo, 2020)
This paper focuses on personal statements written by 23 Year 11 students about what outdoor recreational activities they participated in and their sense of cultural identity in the culturally plural context of Australia.. A sociological approach of inductive analysis of their comments was employed to investigate the extent to which those of culturally diverse identities were actually participating in outdoor recreational activities. The respondents came from six Adelaide co-educational secondary schools which agreed to participate in the study. The responses given to the guideline questions provided evidence of participation in twelve different outdoor recreational activities, some involving individual pursuits and others group activities. Twelve students identified themselves as 'mainstream Australian', while eight claimed identities linked to other European and Asian cultural groups and three reported no sense of cultural identification. The evidence from this exploratory study was that those of culturally diverse identities were actually participating in outdoor recreational activities. However, they were more likely to be involved in individual rather than group activities. Furthermore they preferred land-based activities to those requiring water skills. The paper discusses the significance of the findings, implications for making future initiatives and policies in outdoor recreational activities more inclusive, as well as directions for further research.